WAYS TO WORK ON THE PIANO IN EXTRACURRICULAR ACTIVITIES (Web of Teachers: Inderscience Research, 2024)
This article covers the methods of working on the piano instrument in extracurricular activities, it contains information about the history of the creation of the piano instrument and how it has been preserved to this day.